Validation of the Korean version of the Perinatal Infant Care Social Support scale: a methodological study - Mihyeon Park; Hyeji Yoo; Sukhee Ahn (Korean Journal of Women Health Nursing, 2021)
Purpose The purpose of this study was to develop and test the validity and reliability of the Korean version of the Perinatal Infant Care Social Support (K-PICSS) for postpartum mothers. Methods This study used a cross-sectional design. The K-PICSS was developed through forward-backward translation. Online survey data were collected from 284 Korean mothers with infants 1-2 months of age. The 19-item K-PICSS consists of functional and structural domains. The functional domain of social support measures infant care practices of postpartum mothers. Exploratory factor analysis (EFA) and known-group comparison were used to verify the construct validity of the K-PICSS. Social support and postpartum depression were also measured to test criterion validity. Psychometric testing was not applicable to the structural social support domain. Results The average age of mothers was 32.76±3.34 years, and they had been married for 38.45±29.48 months. Construct validity was supported by the results of EFA, which confirmed a three-factor structure of the scale (informational support, supporting presence, and practical support). Significant correlations of the K-PICSS with social support (r=.71, p<.001) and depression (r=–.40, p<.001) were found. The K-PICSS showed reliable internal consistency, with Cronbach’s α values of .90 overall and .82–.83 in the three subscales. The vast majority of respondents reported that their husband or their parents were their main sources of support for infant care. Conclusion This study demonstrates that the K-PICSS has satisfactory construct validity and reliability to measure infant care social support in Korea.